Kepatuhan Pemakaian Alat Pelindung Diri (APD) Persalinan pada Bidan di Semarang - Ekawati, Ekawati (Kesmas Indonesia, 2018)
Compliance of Personal Protective Equipment (PPE) Use for Midwives in Semarang Ida Wahyuni dan EkawatiOccupational Safety and Health Department, Faculty of Public Health Diponegoro UniversityCorresponding author: ekawatifkmundip@gmail.com ABSTRACTMidwives as well as workers face the risk of occupational diseases. This risk increases because the midwife exposed to body fluids of pregnant / maternal women such as blood and amniotic fluid. Personal protective equipment is necessary to minimize the risk. The purpose of this study was to describe the compliance of personal protective equipment use on midwife. This was descriptive research with cross-sectional approach. Respondents were all midwives in the primary health care, there were 73 peoples. Data were obtained based on questionnaires. The results showed that 100% of midwives washed hands and put on gloves when handling patients. There were 87.8% of midwifves wear masks; 35.1% wear glasses and only 6.8% wear a hat. Midwives need to improve compliance with the use of personal protective equipment for masks, goggles and hats.Keywords: compliance of personal protective equipment, midwife